Optimizing Reciprocity as a Process and a Result of Service-Learning Partnership - Ambangan, Melody A. (Silliman Journal, 2022)
Reciprocity is a very important issue in service-learning. Servicelearning involves humans—whether they be provider or recipient of service. Students are taught valuable knowledge, fundamental skills, and essential values to survive the real world; thus, a reflection on how both parties could gain equitably from service-learning should be strongly thought of. This is an issue of human protection, where the interest of all humans involved should be put into main consideration. Service-learning should be designed foremost to bring about positive change in the lives of both the learners and the community. Generation of new knowledge through hands-on community engagement could only be meaningful if there is an assurance that the initiative will bring no harm and that there is a just and equitable sharing of gains and benefits. This paper is written to expound on the optimization of reciprocity and human protection in service-learning and how the traditional informed consent should be elevated a step higher to informed decision to signify the value for respect and people’s self-determination.